Social media and climate-related disaster management in Africa: A force-field analysis - Agwu A. Ejem; Somtochukwu V. Okeke; Rachael O. Ojeka-John; Emmanuel T. Adekeye (Jàmbá)
This article reviewed bodies of existing local and international literature to provide multi-level insights into Africa’s readiness to standardise the adoption of social media and associated technologies in managing the numerous climate-related disasters in Africa, including storms, floods and droughts. Social media is making serious inroads in disaster management globally, except in Africa, with countries such as the United States of America, Japan, Haiti, Australia and so on, effectively deploying social media technologies in different cycles of disaster management, particularly since 2010. To encourage disaster management stakeholders in Africa to mainstream the involvement of social media in disaster management, this study examined Africa’s prospects using force-field analysis that assessed the social, financial, policy, technological and other factors that inspire or restrain the effective and comprehensive adoption of social media technologies in disaster management. The force-field analysis demonstrated that disaster management stakeholders in Africa have all the tools and conditions to adopt social media technologies in climate-related disaster management on the continent.